MOTION OF NUBIA RELATIVE TO ANTARTICA SINCE 11 MA: IMPLICATIONS FOR NUBIA-SOMALIA, PACIFIC-NORTH AMERICA, AND INDIA-EURASIA MOTION - Royer J.-Y.; Gordon R.G.; Horner-Johnson B.C. (My University, 2006)
Recent estimates of the rotation between Nubia and Somalia have resulted in disparate poles of rotation for the motion since 3.16 Ma (southwest of South Africa) compared with that since 11.03 Ma (near the east tip of Brazil). Here we use magnetic anomaly profiles unavailable in prior Nubia-Antarctica motion studies to significantly revise the estimate of the rotation between Nubia and Antarctica since 11.03 Ma. We use this newly estimated rotation to construct revised estimates of Nubia-Somalia, Pacific-North America, and India-Eurasia motion. The new Nubia-Somalia rotation indicates substantial displacement of Somalia relative to Nubia over the past 11.03 m.y.: 129 ± 62 km extensional, 90 ± 42 km right-lateral transtensional, and 52 ± 21 km right-lateral transtensional near the northern extremity of the East African Rift, the northern Mozambique Basin, and the Andrew Bain Fracture Zone complex, respectively. The substantial rotation between Nubia and Somalia implies that prior plate motion estimates based on a circuit through Africa are biased by 60-85 km at 11.03 Ma and perhaps by much more for earlier reconstructions. Our results imply that India-Eurasia motion since 11.03 Ma has been ~12% (~5 mm yr-1) slower than, and ~20° clockwise of, estimates that neglect Nubia-Somalia motion. Our results further imply that Pacific-North America displacement since 11.03 Ma has been 5°-10° clockwise of prior estimates and require 58-75 km less extensional displacement across the Basin and Range since 11.03 Ma than inferred before. © 2006 Geological Society of America.
Keywords: INDIA-EURASIA MOTION; NUBIA-SOMALIA MOTION; PACIFIC-NORTH AMERICA MOTION; SOUTHWEST INDIA RIDGE